The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cta.2526
|View full text |Cite
|
Sign up to set email alerts
|

A rail‐to‐rail low‐power latch comparator with time domain bulk‐tuned offset cancellation for low‐voltage applications

Abstract: SummaryLow‐voltage high‐precision comparators are the main building blocks of many low‐power mixed‐mode electronic devices. In this paper, a rail‐to‐rail high‐precision comparator is introduced. The proposed comparator uses 2 parallel input P‐type metal‐oxide‐semiconductor pairs with a dynamic level shifter to ensure rail‐to‐rail operation. Moreover, the proposed circuit incorporates a rail‐to‐rail offset cancellation circuit. The offset cancellation circuit works based on a time domain bulk‐tuned negative fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…36,37 Therefore, it is very important to design an extremely low offset comparator for the SoC sensor array. In order to reduce input referred voltage (noise) in comparator circuits, it often to design digitally time-sequence switch and very complex techniques to overcome the kickback noise and input offset voltage [38][39][40][41][42] in comparator, and assisted with calibration scheme. [43][44][45] The input referred offset variation due to the capacitive path from ion sensing to the input stage circuit in SoC can degrade the overall performance of the system, for example, the input referred offset voltage shifts the background reference voltage levels in ADC, and result in the erroneous conversion process.…”
Section: Ph Sensing Principle and The Proposed Dual Offset Cancelation In Double Tail Comparatormentioning
confidence: 99%
“…36,37 Therefore, it is very important to design an extremely low offset comparator for the SoC sensor array. In order to reduce input referred voltage (noise) in comparator circuits, it often to design digitally time-sequence switch and very complex techniques to overcome the kickback noise and input offset voltage [38][39][40][41][42] in comparator, and assisted with calibration scheme. [43][44][45] The input referred offset variation due to the capacitive path from ion sensing to the input stage circuit in SoC can degrade the overall performance of the system, for example, the input referred offset voltage shifts the background reference voltage levels in ADC, and result in the erroneous conversion process.…”
Section: Ph Sensing Principle and The Proposed Dual Offset Cancelation In Double Tail Comparatormentioning
confidence: 99%
“…An energy‐efficient pipelined ADC is deeply reliant on the energy‐efficient comparator 28 . So in this structure, we have designed a latch with maximum power efficiency and minimum delay of output voltage.…”
Section: Proposed Overall Structurementioning
confidence: 99%
“…An energy-efficient pipelined ADC is deeply reliant on the energy-efficient comparator. 28 So in this structure, we have designed a latch with maximum power efficiency and minimum delay of output voltage. Figure 15 demonstrates the schematic diagram of the proposed dynamic double-tail comparator which is used in the subcontrol block.…”
Section: Proposed Double-tail Dynamic Latch For Subcontrol and Sub-adcmentioning
confidence: 99%
“…It can be shown that in the comparison cycle, the current flowing through the input devices are dependent on the input voltages [20]. However, the maximum current is limited by the tail current.…”
Section: B) Comparison Cyclementioning
confidence: 99%